Acute Effect of Pure Oxygen Breathing on Diabetic Macular Edema. Issue 1 (January 2013) - Vinten, Martin; La Cour, Morten; Lund-Andersen, Henrik; Larsen, Michael
Purpose: A small-scale pilot study of the pathophysiology of diabetic macular edema (DME) was made by assessing concomitant changes in macular volume (MV), mean arterial blood pressure (MABP), intraocular pressure (IOP), retinal artery diameter (RAD), and retinal vein diameter (RVD) in response to 120 minutes of pure oxygen breathing. Methods: Eleven eyes of 11 patients with DME were examined at baseline and while breathing pure oxygen for 120 minutes followed by 120 minutes of breathing atmospheric air. Macular volume was determined by optical coherence tomography, retinal trunk vessel diameters by fundus photography, intraocular pressure by pulse-air tonometry, and arterial blood pressure by sphygmomanometry. Results: After initiation of pure oxygen breathing, reductions of 2.6% in RAD (p=0.04) and 11.5% reduction in RVD (p<0.001) were observed while MABP increased by 5.2 mmHg. After resumption of atmospheric air breathing, RAD and RVD rapidly returned to baseline values whereas MABP remained 2.3 mmHg higher than baseline (p=0.04). Macular volume was found to be reduced by 1.2% compared to baseline (p=0.04) at 120 minutes after cessation of pure oxygen breathing and resumption of atmospheric air breathing. Conclusions: These results indicate that the vasomotor response of the retinal arteries alone cannot explain the delayed reduction in macular volume after short course of pure oxygen breathing.